PERUBAHAN GAYA HIDUP SOSIAL MASYARAKAT PEDESAAN AKIBAT GLOBALISASI DI DESA RASI KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Ohy, Grafita; Kawung, Evelin J. R.; Zakarias, Jhon D. (HOLISTIK, Journal Of Social and Culture, 2020)
Globalization is all about the aspect of human life, one of the important aspects of globalization's influence is lifestyle change. Individuals who rapidly absorb information developments will tend to behave following the era of globalization. Fashion becomes one of the target individuals who have a desire to follow the trend, various media such as magazines, television, even many internet sites that offer the desired products. The change in fashion happens periodically tends to form individuals into consumptive up to the very frequent stages of spending intensity.In addition to lifestyle shopping community or family lifestyle can also be seen in daily activities. For example in the form of the social gathering they compete, there is no shopping at home but filling the social gathering like weekly, Monthly and others. While the lifestyle through consumptive life patterns can be seen from the way of shopping the community to meet the basic needs, both food, clothing, housing and others. Style.The consumptive life pattern is the desire to consume items that are less needed excessively just to find the satisfaction side. Indeed, consumptive behavior has a lot of negative effects than positive. The consumptive life patterns in the village of Rasi can be seen in some members of the youth whether in fashion, clothing or possession of luxury items such as the influence of Android HP that has struck the youth today.Â Keywords: globalization, lifestyle, consumptive